Thin film materials behavior under transient laser heating - Lee, Jia Jing (Nanyang Technological University, 2020)
In this project, the thermal behaviors of thin film materials such as polymethylmethacrylate (PMMA), tetrabutylammonium hexafluorophosphate (TBAHFP), and F127 triblock copolymer were studied. Firstly, the samples were dissolved in appropriate solvents and spin-coated on a tungsten-coated-glass substrate. Subsequently, the thin film samples underwent transient heating by a scanning laser beam. The laser source used in the experiments was a 532 nm wavelength continuous wave semiconductor laser. The samples were heated under various parameters such as laser power and heating dwell. Subsequently, the surface morphology of the thin film samples were studied by using an Olympus Optical Microscope. Lastly, from thin film materials heating behaviors we approximated the empirical laser power–dwell–temperature correlations.